Aboud Al-Haimus And His Political Role In The History of Iraq (1904-1989) (Journal of the College of Basic Education, 2025)
Studying political figures is very important for understanding political events, as those who control historical events are individuals, so it is essential to study their political career. Sheikh Aboud Al-Heimis is one of the important figures, and his presence in politics was not coincidental; rather, it was a political necessity imposed on the people for a class of tribal leaders loyal to the regime to reach power, whether through nomination or election. Moreover, the ruling regime's desire to dominate the legislative institution is evident, as most tribal leaders (the feudal lords) are deputies, and we often find their proposals to be primitive or focused on their personal interests. However, Sheikh Al-Heimis did have national stances and varied proposals in which he discussed social and economic issues in the parliamentary council.